2020
DOI: 10.1186/s12967-020-02291-2
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Salivary microbiome of the Qatari population

Abstract: Background: The role of the human microbiome in human health and disease has been studied in various body sites. However, compared to the gut microbiome, where most of the research focus is, the salivary microbiome still bears a vast amount of information that needs to be revealed. This study aims to characterize the salivary microbiome composition in the Qatari population, and to explore specific microbial signatures that can be associated with various lifestyles and different oral conditions. Materials and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 92 publications
2
46
2
Order By: Relevance
“…Murugesan et al [ 25 ] analysed the relative abundance of the salivary microbiome in 997 volunteers, revealing that the elderly ones (people older than 65 years old) showed a lower bacterial richness and diversity as compared with their adult counterparts, aged under 65 years old.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Murugesan et al [ 25 ] analysed the relative abundance of the salivary microbiome in 997 volunteers, revealing that the elderly ones (people older than 65 years old) showed a lower bacterial richness and diversity as compared with their adult counterparts, aged under 65 years old.…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Murugesan et al [ 25 ] determined the salivary bacterial composition of the Qatari population by analysing 997 saliva samples collected from a group of adult (aged at least 18 years) volunteers composed of 442 males and 555 females. Furthermore, the authors aimed to assess the role played by factors such as gender, age (as previously shown), oral health, smoking, and some dietary habits in the salivary microbiome composition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, saliva, which can be sampled with ease and non-invasively, portrays the composition of the oral microbiota and harbors relevant inflammatory markers [13,14]. Importantly, the composition of the salivary microbiota and salivary levels of inflammatory markers have been demonstrated not only to reflect oral health status [15,16], but also to be susceptible to external stress such as oral hygiene discontinuation, smoking and diet [17][18][19]. Therefore, analysis of the salivary microbiota and salivary levels of inflammatory markers is an elegant model system to study the impact of coordinated perturbations on oral homeostasis.…”
Section: Introductionmentioning
confidence: 99%